(3GdaJGhi GdSgejI aj GHf JjejIs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf eG Jbhd GdSGOI GdYdeGA ai QLd jbGd dg CMeO Hf JjejI s
(3BNQgG (B:s
(3hbO ESJhai GdeLjH ChdkG , CHbGg Gddg JYGdi , hdG MGLI Edi GdRjGOg Ydjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3CLGH HgG LeGYI ef GdYdeGA , efge Jbi GdOjf GdMUfi , hfLe GdOjf Hf MLi , hHQgGf GdOjf NWjH YPQG (B- (3Yf QCi GHf JjejI ai RjGQI bHQ GdfHi Udi Gddg Ydjg hSde , hajef JhSd HZGFH Ch ejJ s
(3GdfSNI HgG MhGT s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdCSJGP GdOcJhQ ESMGb ehSi GdMSfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs